Исследование проволочного радиатора с тепловыми трубами для средств вычислительной техники - Bulavin, L. A.; Nikolayenko, Т. Yu.; Nikolayenko, Yu. Е. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
One approach to improving heat dissipation efficiency from computing components such as high-performance microprocessors is proposed. A prototype wire radiator was studied, consisting of copper wire with a diameter of 0.12 mm wound around a frame of two heat pipes, each 6 mm in diameter and 500 mm long. It was shown that the temperature drop along the heat pipe is nearly 60 times smaller than that of a solid copper rod and 200 times smaller than that of a copper tube of the same dimensions. The use of wire finning allowed the average temperature in the heating zone to be reduced by an additional one-third at a heater power of 49.2 W.